2023
DOI: 10.1002/anie.202217735
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Allylmagnesium Reagents by Hydromagnesiation of 2‐Aryl‐1,3‐dienes

Abstract: A protocol for the generation of allylmagnesium reagents from 2‐aryl‐1,3‐dienes was developed using magnesium hydride (MgH2) that is generated in situ by solvothermal treatment of sodium hydride (NaH) and magnesium iodide (MgI2) in tetrahydrofuran (THF). Downstream functionalization of the resulting allylmagnesium reagents with carbonyl compounds or alkyl (pseudo)halides delivers branched products having an allylic quaternary carbon center, whereas that with chlorosilanes resulted in formation of linear allyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In contrast, phosphate with a trimethylsilyl group tends to undergo isomerization at the double bond, resulting in Z -diene 4 – 2g . The simplicity and effectiveness of this methodology are further underscored by its widespread adoption in numerous publications [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…In contrast, phosphate with a trimethylsilyl group tends to undergo isomerization at the double bond, resulting in Z -diene 4 – 2g . The simplicity and effectiveness of this methodology are further underscored by its widespread adoption in numerous publications [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…As a distinct mode of approach, the hydromagnesiation of carbon‐carbon unsaturated bonds could potentially offer an atom‐economical way toward organomagnesium reagents [11] . In this context, our group has recently reported that the solvothermal treatment of magnesium iodide (MgI 2 ) with sodium hydride (NaH) in THF induces counter ion metathesis to form reactive magnesium hydride (MgH 2 ), which facilitates the hydromagnesiation of arylalkynes, [12] 1,3‐enynes, [13,14] and 2‐aryl‐1,3‐dienes, [15] affording alkenylmagnesium, allenyl/propargylmagnesium and allylmagnesium species, respectively ( Scheme 1 a ). The resulting organomagnesium complexes could be functionalized with various electrophiles, enhancing molecular complexities starting from readily available and simple starting materials.…”
Section: Introductionmentioning
confidence: 99%